A systematic review on the cardiovascular pharmacology of Emblica officinalis Gaertn. - Hashem-Dabaghian, Fataneh (Tabriz University of Medical Sciences, 2018)

(untitled) (J Cardiovasc Thorac Res)
Introduction: The Emblica officinalis (EO) fruit has traditionally been considered as a cardioactive medication and has demonstrated remarkable cardiovascular effects in the pharmacological literature. The present study systematically reviews EO’s potential for prevention and therapy of cardiovascular diseases (CVD). Methods: PubMed, ScienceDirect, Scopus, Proquest, Ebsco, Google, Google Scholar, Ovid, and Cochrane databases were searched from 1966 to 2017 for the English and non-English literature using the terms including the cognates of EO including amla, Emblic myrobalan, Emblica officinalis, Emblica pectinata , Indian gooseberry, and Phyllanthus emblica together with antioxidant, arrhythmia, cardioprotective, cardiotoxicity, heart disease, heart failure, hyperlipidemia, hypertension, myocardial dysfunction, and oxidative stress. The inclusion criteria were in vitro, animal, and clinical cardiovascular pharmacological studies conducted on EO and full-text accessibility. The exclusion criterion was studies in which a combination of EO and at least one other plant was investigated. The reference lists of the retrieved articles were also searched manually for additional eligible articles. The methodological quality of clinical trials was assessed by the Jadad scale, and animal studies were evaluated by the ARRIVE checklist. Results: Nineteen articles concerning the cardiovascular pharmacological effects of EO were included in this review. The plant has shown antiatherogenic, anticoagulant, hypolipidemic, antihypertensive, antioxidant, antiplatelet, and vasodilatory effects as well as lipid deposition inhibitory properties. Moreover, it prevents from doxorubicin and isoproterenol cardiotoxicity and myocardial ischemia/reperfusion injury, and improves vascular endothelial function in animal studies. Some high-quality clinical studies report the vasodilatory and myocardial antioxidant properties as well as anti-platelet aggregation effects of this plant. Conclusion: EO influences various cardiovascular risk-factors. However, there is not sufficient evidence to confirm the plant efficacy in preventing and treating CVD.